2022
DOI: 10.1007/s12471-022-01677-9
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of vaccination against COVID-19 outweighs the potential risk of myocarditis and pericarditis

Abstract: Vaccines against coronavirus 2019 disease (COVID-19) have shown to be greatly effective in preventing viral spread, serious illness and death from this infectious disease and are therefore critical for the management of the COVID-19 pandemic. However, the listing of myocarditis and pericarditis as possible rare side effects of the messenger RNA (mRNA) vaccines against COVID-19 by regulatory agencies has sparked discussion on the vaccines’ safety. The most important published cohort studies to date demonstrat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…These suggest an elevated risk of myocarditis and potentially pericarditis in the first 7–14 days after vaccination, especially in younger men after the second dose. Most of the cases resolved without problems ( EMA press office, 2021 ; Klamer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These suggest an elevated risk of myocarditis and potentially pericarditis in the first 7–14 days after vaccination, especially in younger men after the second dose. Most of the cases resolved without problems ( EMA press office, 2021 ; Klamer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of COVID-19 vaccine induced myocarditis is 1–4 cases per 100,000 vaccinated individuals. 54 In 95% of these cases, cardiac markers, echocardiographic and electrocardiographic markers will show a downward trend and eventually subside in few days with complete remission without any sequelae. 54 A systematic review and meta-analysis demonstrated that the risk of myocarditis is 7 times more apparent in COVID-19 patients [RR: 15 (95% CI: 11.09–19.81] as compared to vaccination group RR: 2 (95% CI: 1.44–2.65).…”
Section: Discussionmentioning
confidence: 99%
“…A view of the WHO's COVID-19 dashboard (2) shows four cycles of cases, with peaks in January, April, and August 2020 and January 2022 (and possibly in March 2022) (Figure 1), the precise reasons for which are unclear but may reflect the differing infectivity of variants of the original SARS-CoV-2. Similarly, there were peaks in the number of deaths in January (103,228 in the week of 18 January), April (96,071 in the week of 26 April), and August 2021 (71,012 in the week of 23 August), with a fourth in February 2022 (76,118 in the week of 7 February), which may reflect a combination of the infectivity and lethality of the variants.…”
Section: The Three Wavesmentioning
confidence: 97%
“…Similarly, the pre-pandemic incidence of clinical myocarditis in the general population is around 13/million. The incidence in those hospitalised and unvaccinated with SARS-CoV-2 is 2261/million, but the incidence in those vaccinated = 21/million ( 76 ). The incidence ratio for pulmonary embolism has been reported as being 1.21 (95% CI, 1.07–1.36) after vaccination with BNT162b2, consistent with that seen after ChAdOx1 vaccination.…”
Section: Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation